Mindfulness-based interventions modulate structural network strength in patients with opioid dependence - Fahmy, Reham; Wasfi, Maha; Mamdouh, Rania; Moussa, Kareem; Wahba, Ahmed; Wittemann, Miriam; Hirjak, Dusan; Kubera, Katharina Maria; Wolf, Nadine D.; Sambataro, Fabio; Wolf, Robert Christian (Addictive behaviors, 2018)
Mindfulness-based interventions (MBI) are increasingly used in the treatment of patients with mental disorders, in particular in individuals presenting with affective disorders or in patients exhibiting abnormal levels of impulsive behavior. MBI have been also offered to patients with substance use disorders, where such treatment options may yield considerable clinical effects. Neural effects associated with MBI have been increasingly acknowledged, but is unknown whether MBI exert specific effects on brain structure in patients with substance use disorders. In this study, we investigated 19 inpatients with opioid dependence receiving treatment-as-usual (TAU, n=9) or additional MBI (n=10). Structural magnetic resonance imaging data were acquired before and after four weeks of treatment. Source-based morphometry was used to investigate modulation of structural networks after treatment. Both treatment modalities led to significant clinical improvement. Patients receiving MBI showed a significant change in distress tolerance levels. An increase in bilateral striatal/insular and prefrontal/cingulate network strength was found in patients receiving MBI compared to individuals receiving TAU. Prefrontal/cingulate cortical network strength was associated with impulsivity levels. These findings suggest that MBI can have a recognizable role in treatment of substance use disorders and that neural effects of MBI may be captured in terms of frontostriatal structural network change.